The Effect of Tax Knowledge and Tax Sanctions on Tax Compliance in SMEs in Sungai Penuh City - Abdallah, Zachari; Rafiqi, Aufa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to see the effect of Tax Knowledge, Tax Sanctions on Tax Compliance in MSMEs in Sungai Penuh City, The independent variables consist of tax knowledge and tax sanctions, the dependent variable is tax compliance in MSMEs. Data collection techniques by distributing questionnaires and obtaining 176 respondents, this study uses multiple linear analysis methods and the F Test (Simultaneous Significance Test) processed with SPSS 24, The results of this study indicate that tax knowledge has an effect and is significant to tax compliance of 8.010. Tax sanctions have a significant effect on tax compliance of 8.832. While simultaneously tax knowledge, tax sanctions have a significant effect on tax compliance of 0.000.